Alterations in circulating lipidomic profile in patients with type 2 diabetes with or without non-alcoholic fatty liver disease - Alfadda, Assim A.; Almaghamsi, Abdulrahman M.; Sherbeeni, Suphia Murad; Alqutub, Adel N.; Aldosary, Abdullah S.; Isnani, Arthur C.; Al-Daghri, Nasser; Taylor-Robinson, Simon D.; Gul, Rukhsana (Frontiers in Molecular Biosciences, 2023)
Abstract Objective: Non-alcoholic fatty liver disease (NAFLD) and Type 2 diabetes mellitus (T2DM) often coexist and drive detrimental effects in synergistic manner. This study was designed to understand the changes in circulating lipid and lipoprotein metabolism in patients with T2DM with or without NAFLD. Methods: Four hundred thirty-four T2DM patients aged 18 to 60 years were included in this study. Fatty liver was assessed by FibroScan. The comprehensive metabolic lipid profiling of serum samples was assessed by using high-throughput proton NMR metabolomics. Results: Our data revealed significant association between steatosis and serum total lipids in VLDL and LDL lipoprotein subclasses, while total lipids in HDL subclasses were negatively associated. A significant positive association was found between steatosis and concentration of total lipid, phospholipids, cholesterol and triglycerides in VLDL and LDL subclasses, while HDL subclasses were negatively associated. Furthermore, a significant, association was observed between fibrosis and concentrations of total lipid, phospholipids, cholesterol and triglycerides in very small VLDL, large and very large HDL subclasses. Conclusion: The metabolomics results provide evidence that patients with T2DM with higher steatosis grade have altered lipid metabolomics compared to patients without steatosis. Increased lipid, phospholipids, cholesterol and triglycerides concentration of VLDL and LDL subclasses are associated with steatosis in patients with T2DM.